Sovereign Authority and the Elaboration of Law in the Bible and the Ancient Near East - Johnson, Dylan R. (Mohr Siebeck, 2020)
Souveräne Autorität und die Ausarbeitung des Rechts in der Bibel und im Vorderen Orient.
PublicationDate: 20200826
Keywords: Book of Numbers -- Torah -- coinage -- Holiness Code -- Porträt Gottes -- Priestly Tradition -- Altes Testament -- Altorientalistik -- Religion und Recht -- Array